(untitled) (Libya Journal of Geographical Studies, 2023)
The research aims to verify extent of soil sensitivity to wind erosion in governorate of Taiz, and identify areas most affected by soil wind erosion in governorate during dry season between (October - May) 2018. The research methodology was represented by using dust index, to derive information layers that show soil sensitivity to wind erosion in dry season, from remote sensing data, represented by satellite image of MODIS Terra, obtained from the NASA website. and applied this index to bands of satellite image that used in determining areas of dust spread, or areas where its soil suffer of sensitive highly of erosion to monthly level. Results of research found that locations of regions affected by risk of wind erosion different from month to month, and therefore area of zone that was exposed to wind erosion during dry season reached 4441.7 km2, percent 44.3% of total area of governorate. and area of most affected by wind erosion reached 771.4 km2, percent 7.7% of total area of governorate. The research concluded that spatial variation of soil sensitivity to wind erosion in governorate, It is due to properties of soil, and change in cohesion strength of its grains from one month to another, due to practice of plowing, soil moisture, and extent cover vegetation and agriculture. with other climate variables particular, variation in wind speed, and precipitation rates, temperature, dryness severity, and humidity level.